Every fifth patient suffered a high nutritional risk—Results of a prospective patient survey in an oncological outpatient center - Jendretzki, Julia; Henniger, Dorothea; Schiffmann, Lisa; Wolz, Constanze; Kollikowski, Anne; Meining, Alexander; Einsele, Hermann; Winkler, Marcela; Löffler, Claudia (Frontiers in Nutrition, 2022)
Introduction Malnutrition in cancer patients often remains undetected and underestimated in clinical practice despite studies revealing prevalences from 20 to 70%. Therefore, this study aimed to identify patient groups exposed to an increased nutritional risk in a university oncological outpatient center. Methods Between May 2017 and January 2018 we screened oncological patients there using the malnutrition universal screening tool (MUST). Qualitative data were collected by a questionnaire to learn about patients’ individual information needs and changes in patients’ diets and stressful personal nutrition restrictions. Results We included 311 patients with various cancers. 20.3% (n = 63) were found to be at high risk of malnutrition, 16.4% (n = 51) at moderate risk despite a mean body mass index (BMI) of 26.5 ± 4.7 kg/m2. The average age was 62.7 (± 11.8) with equal gender distribution (52% women, n = 162). In 94.8% (n = 295) unintended weight loss led to MUST scoring. Patients with gastrointestinal tumors (25%, n = 78) and patients >65 years (22%, n = 68) were at higher risk. Furthermore, there was a significant association between surgery or chemotherapy within six months before survey and a MUST score ≥2 (OR = 3.6). Taste changes, dysphagia, and appetite loss were also particular risk factors (OR = 2.3–3.2). Young, female and normal-weight patients showed most interest in nutrition in cancer. However, only 38% (n = 118) had a nutritional counseling. Conclusion This study confirms that using the MUST score is a valid screening procedure to identify outpatients at risk of developing malnutrition. Here one in five was at high risk, but only 1% would have been detected by BMI alone. Therefore, an ongoing screening procedure with meaningful parameters should be urgently implemented into the clinical routine of cancer outpatients as recommended in international guidelines.